Application Of Jigsaw Type Cooperative Learning Model To Learning Outcomes And Motivation In Colloidal Materials Assisted By Practicum At SMA Negeri 1 Laubaleng - Ginting, Tasya; Ginting, Elfrida (Jurnal Pendidikan dan Pembelajaran Kimia, 2024)
Abstract:Application of Jigsaw-type Cooperative Learning Model to Learning Outcomes and Motivation in Pratctic-Assisted Colloidal Materials at SMA Negeri 1 Laubaleng. The learning model is a certain pattern or learning steps applied by teachers so that the goals of learning are achieved. The learning model applied in this study is a jigsaw-type cooperative learning model. The purpose of this study is to find out whether there is an increase in learning outcomes, student learning motivation and there is a significant correlation between learning motivation and student learning outcomes learned with a jigsaw-type cooperative model assisted by practicum on colloidal materials. The sample in this study was taken from two classes, namely class XI Science 1 which is called the experimental sample of 34 students who are taught with a jigsaw-type cooperative model assisted by practicum and XI Science 3 which is called the control sample of 34 students who are taught with a conventional model assisted by practicum, the sample is determined by random sampling technique, the results of the study show that the average learning outcome of students in the experimental class is 86.47 while the students in the control class 65.29; The average motivation of students in the experimental class while the students in the control class was 78.35 while the students in the control class were 64.24 and there was a significant correlation between student learning motivation and student learning outcomes learned by the JIGSAW-type cooperative model assisted by practicum, with a correlation coefficient of 0.92 and the contribution of student motivation to the improvement of student learning outcomes by 85% while 15% was influenced by other factors.Keywords: Jigsaw Type Cooperative, Learning Motivation, Learning Outcomes, Practicum, Colloid.DOI: 10.23960/jppk.v13i1.30278